A case of Pompe disease in infant - E. F. Sudorgina; S. B. Choloyan; M. V. Sheenkova; L. P. Kolesnikova (Нервно-мышечные болезни)
A case of Pompe disease in infant in Orenburg is presented in this article. Clinical picture of the infantile form of the disease is described. Enzyme replacement therapy (ERT) with alglucosidase alfa is presented (alglucosidase alfa is not registered in Russia, was administered due tolife-threatening indication). Nowadays ERT is the only possible pathogenetic treatment of Pompe disease.